PERPUSTAKAAN MADRASAH NEGERI DI JAKARTA DAN PERMASALAHANNYA - Pudjiharti Pudjiharti (Jurnal IPI (Ikatan Pustakawan Indonesia), 2015)
Libraries play very important roles in providing access for learners to achieve their learning success; therefore library existence at schools becomes one of the keys to successful teaching-and-learning proccess. But in fact, school libraries in Indonesia have not been able to carry out their utilities and functions to support the learning process. The objective of this study is to find out the quality profile of State Madrasah Libraries ncluding room facilities, human resources, book collections, services and budgets. Furthermore, this study also presents whether the school-library supporting items meet the standardized requirements of the National Eduction Standards (2005) and the Library Regulations (2007). The Descriptive method is implemented at the Stat< lslamic Senior High school (MAN), State Islamic Secondary School (MtsN), and State lslamic Primary School (MIE, ). There are 61 state-madrasah libraries observed in Jakarta areas. The study was carried out for 3 months -from March to May 2012. The result has shown that every madrasah has provided each library with a special room. However, almost 10% of the libraries are attached to another room. It is also found that the ideal library room is a ailable in only 8% out of the 61 respondent libraries. Additionally, the human resources of those libraries who lave bachelor degree-holder in Library are only 7% in MAN and 9% in MTsN but none in MIN. So those libraries are mostly managed by non-library bachelor-degree holders. In other words, they are teacher who act as librarians and are supported by 1-2 technical assistants who graduated from senior high school. Those technical assistants have joined and attended some library technical trainings. But, only 15% of them meet the required standards. Some libraries that have met a standard collection are only 10%, with the ratio of 60:40 for t ie non-fiction collection and fiction. The utilization of information technology in library operational system is s ill limited. The IT (Information Technology) is implementend only in the library materials processing (29%). Sorce of them use Senayan library software and some of them use other library softwares. The whole sectors the users are carried out manually. Circulation book services are performed by all the madrassah. However, internet services, story telling, and reader guidance are endorsed only by 16% madrasah. Only 8% of madrasahs finance their library budget which is taken at least 5% of the total school operational budget. In general, this study concludes that the surveyed madrasahs libraries do not meet the library quality standard. However, there are 5 MAN potential libraries that could be improved to meet to the national standard.